Sustainability aspects in real estate management – basics and opportunities for an indicator-based target and reporting system in real estate companies - Matthias Buchholz; Thomas Lützkendorf (Acta Polytechnica CTU Proceedings, 2022)
The challenge for real estate companies to assess and communicate sustainability aspects at corporate, portfolio and building level is constantly increasing due to many external and internal influences. Corresponding requirements address the sustainability reporting of the company or the environmental performance of the building stock for example. In order to meet legal requirements and to stay competitive, companies use specialisation techniques. One possibility is provided by indicators which can help to gather, assess and communicate sustainability aspects. This paper investigates the information flows between different decision levels of Real Estate Management (REM) that can be established with the help of indicators. The results reveal the relevance of indicators for a horizontal as well as for a vertical integration of sustainability-related information in REM. Moreover, synergies for the development and interpretation of indicators across decision levels can be identified by taking into account measuring units, reference units and system boundaries. Results from a research that reflects the situation in Germany and considers current developments in the EU will be presented.